THE INFLUENCE OF DISCIPLINE AND MOTIVATION ON WORK PRODUCTIVITY - Dharliana Dharliana; Sandi Nasrudin Wibowo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This researcher aims to test Work Motivation and Work Discipline against the Work Productivity of PD Sri Tanjung Indramayu. The research method used in this study is a quantitative method. The population in this study was PD Sri Tanjung Indramayu employees totaling 67 employees. This research sampling technique uses saturated sampling. The data withdrawal technique uses questionnaires and the data analysis used is multiple regression analysis. The results of the researchers showed that there was a positive and significant influence between the variables of Work Motivation on Work Productivity in terms of the -tcount of the < -ttable, namely 13,014 < 1,997 with a sig of 0.000 < 0.05. The results of this study also show that work discipline has a positive and significant effect on work productivity as seen from the –t count of the < -t table, namely 11,014 < 1,997 with a sig value of 0.005 < 0.5 by means of simultaneous variables Work Motivation and Work Discipline have an effect and significant effect on work productivity shown by F calculate > F table, which is 94.615.